Analysis of Quality Control of White Tofu Products Using the Six Sigma Method at the Tofu Factory UD. Al Jaliil in Balikpapan City - Aini, Qurrotul; Djamali, Abdoel; Malik, Amalia (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
UD Al Jaliil is one of the agro-industry producers of white tofu in Balikpapan City. The challenge faced in maintaining quality is that defective products are still found. To handle this problem, UD AlJaliil needs to carry out quality control methods Six Sigma.  This research aims to 1) analyze the implementation of quality control at UD Al Jaliil using methods Six Sigma 2) Determine the DPMO value and level Sigma white tofu products 3) Identify the factors that cause defective products so that efforts can be made to improve the quality of white tofu. Quality control is carried out using methods Six Sigma. Six Sigma  is a quality control method by reducing the level of defects through five stages of DMAIC, namely Define, Measure, Analyze, Improve and Control. The results of the research show that the processes at UD Al Jaliil are not yet completely under control because processes are still found that are outside the control limits. The DPMO value is 306,300 units/process, meaning that in one million products produced there is the possibility of 306,300 defective products. Level Sigma UD Al Jaliil is 2.0064 Sigma. And there are several factors that cause defects in the texture of white tofu, namely factors man, machine, method, material and environment.